Muslim Adolescents and the Islamic Identity Crisis in the Urban Environment of Tarai Bangun, Riau - Khotimah; Salmaini Yeli; Imron Rosidi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
Rapid urbanization and social heterogeneity in urban areas frequently trigger dynamics of religious identity crises among adolescents. This study aims to describe the forms of Islamic identity crisis, analyze its contributing factors, and explore the adaptation strategies employed by Muslim youths in Tarai Bangun Village, Kampar Regency. A descriptive qualitative approach was employed, utilizing in-depth interviews, participatory observation, and Focus Group Discussions (FGDs). The findings reveal that the identity crisis experienced by adolescents is not a rejection of Islamic teachings, but rather a dynamic transition from a normative, family-inherited identity toward a reflective Islamic identity constructed through exploration, negotiation, and commitment to Islamic values. This identity development evolves through three distinct stages: normative understanding (ages 12–14), social-moral expansion (ages 15–17), and reflective internalizations (ages 17–18). The primary drivers of this crisis include value discrepancies between home, school, and peer environments, exacerbated by urbanization, social media exposure, peer pressure, and a lack of supportive mentorship. This study underscores the need for comprehensive adaptation strategies that integrate Islamic digital literacy, family guidance, community support, and Islamic psychological approaches to foster an adaptive socio-religious identity amid modern challenges.